Nitrogen activation to reduction on a recyclable V-SAC/BN-graphene heterocatalyst sifted through dual and multiphilic descriptors - Maibam, Ashakiran; Krishnamurty, Sailaja (Journal of Colloid and Interface Science, 2021)
<span style="color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Efficient reduction of nitrogen to ammonia at a minimal cost would require a recherche catalyst tailored by assimilating the inherent electronic and reactive nature of Single Atom Catalysts (SACs) on heteroatom doped-graphene. A full-scale DFT study accounting for disparate descriptions of atomic orbitals and representation of support, has been carried out to identify the most active and recyclable SAC/B-graphene composite as catalyst for Nitrogen Reduction Reaction (NRR). Dual and Multiphilic descriptors derived reactivity pattern of six different metal SACs V, Fe, Ni, Ru, W and Re on periodic and non-periodic paradigms of pristine and BN-pair doped graphene supports, align with the calculated chemisorption efficacy and activation of N<span style="box-sizing: inherit; font-size: 12px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">. The enzymatic route of nitrogen reduction on three most ideal metal SACs (V, W and Re) culminates Vanadium SAC, a relatively cheaper metal, anchored on BNring-graphene with an energy barrier of ⩽1.24 eV as a highly active and recyclable catalyst for NRR.